Patterns of executing budgeting as a tool of planning and control: with special reference to listed companies in Sri Lanka - Indrani, M.W.; Wickremasinghe, G.; Naidoo, Moonsamy (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
In the modern business world, budgets accomplish a significant role both in planning and control of businesses towards attaining organizational goals. The purpose of this study is to investigate patterns of executing budgeting technique by different companies/industry sectors, in realizing intended purposes. Applying Mixed Method Research (MMR) approach, data for this study was collected through questionnaire survey and discussions with financial executives of 42 listed companies representing five sectors. In view of the major types of simultaneous and sequential mixed methods deigns, this research is concerned with two paradigms (out of eight paradigms): QUAN + qual and QUAN → qual, respectively. The survey data were analyzed using SPSS software and frequency tables while employing ‘thematic analysis’ and ‘content analysis’ for descriptive data. It identified ‘results point of interface’ as the suitable position for integrating core component ‘QUAN’ and supplemental component ‘qual’ to provide meaningful interpretations and sound conclusions for the study. Patterns of application of budgeting vary to a considerable extent from one another within the industry and between industries. Such differences may be largely attributed to the nature of businesses, impact of environmental changes on business activities, markets served (local or foreign), policies, procedures, and specific circumstances that individual companies exercised. Thus, it suggests that these factors may have an impact on the patterns of budgeting practices adopted by individual companies/ industry sectors. Findings conclude that budgeting seems to be the most important technique for all companies irrespective of their sector, playing the biggest role for planning than control of businesses. This study provide helpful insights and useful guidelines to business entities practicing under different organizational contexts and influences, in applying certain MA techniques i.e. budgeting in a proper way making sure that they are moving on to appropriate direction towards achieving organizational goals and hence business sustainability.
Keywords: Budgeting; Planning; Control; listed companies; Industry sectors